Navigating complex arterial reconstruction in living donor liver transplantation: the role of the splenic artery as a viable conduit - Hosam Hamed; Mohamed Elshobary; Tarek Salah; Ahmad M. Sultan; El-sayed Abou El-Magd; Ahmed M. Elsabbagh; Ahmed Shehta; Mohamed Abdulrazek; Waleed Elsarraf; Mohamed A. Elmorshedi; Mostafa Abdelkhalek; Usama Shiha; et al. (BMC Surgery)
Abstract Background In living donor liver transplantation (LDLT), maintaining hepatic arterial flow is critical for graft survival. Alternative methods are required when the recipient’s hepatic artery is unsuitable due to extensive dissection or inadequate flow. This study evaluates the efficacy and safety of splenic artery transposition (SAT) for hepatic arterial reconstruction in LDLT. Methods This retrospective cohort study included 10 LDLT patients with hepatic arterial reconstruction by SAT to assess operative parameters, postoperative complications, mortality, and patency rate. Results The splenic artery was used because of arterial dissection (70%) or inadequate arterial blood flow. Operative time ranged from 640 to 1020 min, and no splenic infarction was observed. Post-operative complications were as follows; biliary leakage (10%), pancreatitis (10%), intraabdominal hemorrhage (10%), and arterial thrombosis (10%). Mortality in this cohort was 30%, one of them was due to thrombosis of the conduit and the other two died from sepsis-related complications. With a median follow-up of 43 months, this technique was associated with a 70% survival rate. Conclusion The splenic artery is a viable conduit for hepatic arterial reconstruction in LDLT, demonstrating an acceptable safety profile and complication rates. This approach is recommended in cases where the recipient’s hepatic artery is significantly compromised.